2020
DOI: 10.3390/v12050507
|View full text |Cite
|
Sign up to set email alerts
|

Merkel Cell Polyomavirus (MCPyV) in the Context of Immunosuppression: Genetic Analysis of Noncoding Control Region (NCCR) Variability among a HIV-1-Positive Population

Abstract: Background: Since limited data are available about the prevalence of Merkel cell polyomavirus (MCPyV) and the genetic variability of its noncoding control region (NCCR) in the context of immunosuppression, this study aimed to investigate the distribution of MCPyV in anatomical sites other than the skin and the behavior of NCCR among an HIV-1-positive population. Methods: Urine, plasma, and rectal swabs specimens from a cohort of 66 HIV-1-positive patients were collected and subjected to quantitative real-time … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 44 publications
1
14
0
Order By: Relevance
“…Although MCPyV is constantly shed from healthy skin and up to 60-80% of healthy people have antibodies against this virus, MCC is rare with an incidence of 0.2-0.45 cases/100,000 individuals per year in most countries [13]. The MCC incidence increases with aging [31][32][33][34][35] and among immunocompromised individuals such as HIV-1/AIDS patients [15,[35][36][37][38]. To date, the events connecting initial MCPyV infection and subsequent cell transformation remain elusive, although it has been established that viral DNA integration into the host genome and continued expression of the C-terminal truncated LT are required for MCC development [20].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Although MCPyV is constantly shed from healthy skin and up to 60-80% of healthy people have antibodies against this virus, MCC is rare with an incidence of 0.2-0.45 cases/100,000 individuals per year in most countries [13]. The MCC incidence increases with aging [31][32][33][34][35] and among immunocompromised individuals such as HIV-1/AIDS patients [15,[35][36][37][38]. To date, the events connecting initial MCPyV infection and subsequent cell transformation remain elusive, although it has been established that viral DNA integration into the host genome and continued expression of the C-terminal truncated LT are required for MCC development [20].…”
Section: Discussionmentioning
confidence: 99%
“…Total DNA was extracted from urine and plasma using the DNeasy ® Blood & Tissue Kit (QIAGEN, Milan, Italy), according to the manufacturer's instructions. Specific qPCR assays were performed using TaqMan-based qPCR, employing primers and probes for MCPyV sT, as previously described [35]. All samples were tested in triplicate, and the number of viral copies was calculated from standard curves constructed using a ten-fold dilution series of plasmid pMCV-R17a containing the entire genome of MCPyV (Addgene, #24729) (dilution range: 10 8 -10 copies/mL).…”
Section: Mcpyv Dna Extraction and Quantification By Qpcrmentioning
confidence: 99%
See 2 more Smart Citations
“…However, MCPyV NCCR variation affects early and late promoter activities in a VN-MCC cell line and in human dermal fibroblast and wild-type LT inhibited both early and late promoter activities in both cell lines, whereas tLT had the opposite effect [ 25 ]. A recent study demonstrated the onset of insertions and deletions in the NCCR among an HIV-1-positive population [ 26 ]. Whether NCCR variation has an influence on viral replication and pathogenic properties of the virus remains to be investigated.…”
Section: Introductionmentioning
confidence: 99%